Prevalence and epidemiological aspect of dengue fever in western Rajasthan in year 2018 - Kothari, Varun; Rathore, Laxmi; Khatri, P. K.; Meena, Saroj (International Journal of Research in Medical Sciences, 2019)
Background: Dengue fever (DF) is a common mosquito borne disease caused by dengue virus and is transmitted by Aedes mosquito. It is one of the major public health problems in India which affects all levels of society, but the burden of disease is a higher in poor people who live together in communities. Aim of present study is aimed to assess the prevalence and epidemiological characteristics of cases of DF in Tertiary Care Hospitals in Jodhpur, Rajasthan. Methods: A cross-sectional study was conducted in all cases of DF registered in the associated group of Hospitals of Dr. S.N. Medical College, Jodhpur from 1st January 2018 to 31st December 2018. Rapid immune-chromatographic card test and MAC ELISA test method was used to detect dengue non-structural protein 1 (NS1) antigen and dengue immunoglobulin M (IgM) antibodies in the Viral Research Diagnostic Laboratory (VRDL) of Department of Microbiology, Dr. S.N. Medical College to confirm the diagnosis. Results: Out of 2701 patients, 541 patients were tested serologically positive for DF (NS1, IgM). The highest number of suspected cases (1061) was reported in the month of October, 2018 out of whom 228 were positive. Maximum number of dengue cases reported were males belonging to 31-40 years age group from urban area. Fever was the main complaint in all the cases followed by vomiting, headache, and abdominal pain. Conclusion: Dengue is one of the major public health problems in India. A large number of cases are reported in the monsoon and post-monsoon period in the months from September to December. Measures can be taken both at personal and government level to reduce morbidity and mortality from dengue.